Lactate dehydrogenase-elevating virus enhances natural killer cell-mediated immunosurveillance of mouse mesothelioma development - Mandour, Mohamed F. (Infect Agent Cancer, 2020)
BACKGROUND: Viral infections can reduce early cancer development through enhancement of cancer immunosurveillance. This study was performed to analyse this effect of viral infection in a mouse model of solid tumor. METHODS: The experimental model used was the effect of BALB/c mouse infection by lactate dehydrogenase-elevating virus on AB1 mesothelioma cancer development. RESULTS: Acute infection with lactate dehydrogenase-elevating virus strongly reduced in vivo early AB1 mesothelioma growth and death resulting from cancer development. This effect was not due to a direct cytolytic effect of the virus on AB1 cells, but to an in vivo activation of natural killer cells. Gamma-interferon production rather than cytotoxic activity against AB1 cells mediated this protective effect. This gamma-interferon production by natural killer cells was dependent on interleukin-12 production. CONCLUSIONS: Together with other reported effects of infectious agents on cancer development, this observation may support the hypothesis that enhancement of innate immunosurveillance against tumors may result from infection with common infectious agents through modulation of the host immune microenvironment.